2021
DOI: 10.1093/treephys/tpab017
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of mesophyll conductance due to salt stress inPopulus cathayanafemales and males growing under different inorganic nitrogen sources

Abstract: Synergistic regulation in leaf architecture and photosynthesis is essential for salt tolerance. However, how plant sex and inorganic nitrogen sources alter salt stress-dependent photosynthesis remains unknown. Leaf anatomical characteristics and photosynthesis of Populus cathayana Rehder females and males were investigated under salt stress conditions combined with NO3− and NH4+ supplies to clarify the underlying mechanisms. In salt-stressed females, we observed an increased mesophyll spongy cell density, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…However, Sharkey et al (1991) reported that increases in the thickness of the cytosol layer between chloroplasts and cell walls of wild-type tobacco plants, due to changes in the shape of chloroplasts, resulted in significant increases in mesophyll resistance. On a similar note, Liu et al (2021b) speculated that the increased r cyt values, and following decreases in g m , observed in their study were due to the alterations in the shape of chloroplasts under conditions of drought stress. In the current study, a marked increase in r cyt was found in both cultivars under conditions of drought stress (Figure 7), and it was attributed to the considerable increases in the distance not only between the chloroplast and the cell wall (ΔL cyt,1 ), but also between adjacent chloroplasts (ΔD chl ) (Supplementary Figure S4c,d).…”
Section: Discussionmentioning
confidence: 62%
“…However, Sharkey et al (1991) reported that increases in the thickness of the cytosol layer between chloroplasts and cell walls of wild-type tobacco plants, due to changes in the shape of chloroplasts, resulted in significant increases in mesophyll resistance. On a similar note, Liu et al (2021b) speculated that the increased r cyt values, and following decreases in g m , observed in their study were due to the alterations in the shape of chloroplasts under conditions of drought stress. In the current study, a marked increase in r cyt was found in both cultivars under conditions of drought stress (Figure 7), and it was attributed to the considerable increases in the distance not only between the chloroplast and the cell wall (ΔL cyt,1 ), but also between adjacent chloroplasts (ΔD chl ) (Supplementary Figure S4c,d).…”
Section: Discussionmentioning
confidence: 62%
“…The roots, as the first checkpoint for the Na + and K + uptake from the soil, have a key role in reducing the overall plant Na + over‐accumulation and achieving K retention (Chakraborty et al, 2016; Khan et al, 2016). Females had more thin roots and larger root biomass, which intensively explored the soil around their roots (Liu et al, 2021b), thus having a higher ability for nutrient absorption. However, this acquisitive strategy in females may not distinguish ions, which are toxic or necessary for plants (Liu et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Populus species display sexual dimorphisms (Juvany and Munné‐Bosch, 2015; Yu et al, 2018; Liu et al, 2021a). Many studies have suggested that dioecious plants exhibit sex‐related morphological, physiological, and molecular differences in responses to environmental factors, including salt stress (Liu et al, 2021b; Olano et al, 2017). Moreover, sexual differences under abiotic stresses can further be affected by the N status and forms (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The major role of spongy mesophyll in plants is to interchange the required CO 2 for photosynthesis ( Veromann-Jürgenson et al, 2020 ). All spongy mesophylls are covered by a thin layer of water, hence environmental stresses can significantly affect mesophylls resulting in a reduced photosynthesis activity level in plants ( Veromann-Jürgenson et al, 2020 ; Liu M. et al, 2021 ). Therefore, changes in the water and gas level in mesophylls is the first sign of detecting stresses in plants, so the difference between the reflectance of the 730 nm as well as the 820 nm band in normal and stress conditions can be considered as a measurement for abiotic and biotic stresses ( Momayyezi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%